Predictive value of characteristics of resected parathyroid glands for persistent secondary hyperparathyroidism during parathyroidectomy - Yaoyu Huang; Jing Wang; Ming Zeng; Huiting Wan; Ningning Wang; Guang Yang (BMC Surgery, 2023)
Abstract Background Parathyroidectomy (PTX), an effective treatment for refractory secondary hyperparathyroidism (SHPT) in chronic kidney disease (CKD) patients, still has a high persistent rate. This study aimed to analyze the predictive value of characteristics of resected parathyroid glands for postoperative persistent SHPT. Methods The clinical data of patients with persistent SHPT and successful PTX controls who had or underwent total parathyroidectomy with forearm autotransplantation (TPTX + AT) was retrospectively collected. The characteristics including the number, minimum weight, maximum weight and total weight of resected parathyroid glands from each patient were recorded. Characteristics and cutoff value of resected parathyroid glands for the prediction of persistent SHPT were analyzed. Results A total of 227 patients (62 persistent SHPT patients and 165 successful PTX controls) were enrolled in the study. Forty-one (66%) persistent SHPT cases related to supernumerary parathyroid and the remaining 21 (34%) cases related to residual undetected parathyroid. In addition, ectopic parathyroid was found in 8 patients (13%) before PTX. The average number of resected glands in the persistent SHPT group and successful PTX group was 3.53 ± 0.72 and 3.93 ± 0.25 respectively (p < 0.001). There was significance in the number of patients with different resected parathyroid glands between two groups (p < 0.001). When the resected gland number was 4, minimum weight of the parathyroid was noted to be heavier in the persistent SHPT group than that in the successful PTX group (0.52 ± 0.31 g vs. 0.38 ± 0.19 g, p < 0.001). For persistent SHPT prediction, cutoff value of minimum weight was 0.535 g, with sensitivity of 46% and specificity of 82% (AUC = 0.611; p = 0.029). Conclusions Major reason for the persistent SHPT is the existence of supernumerary parathyroid glands or resection of less than 4 glands. When 4 glands were resected, a minimum total parathyroid gland weight heavier than 0.535 g implied the potential presence of a missed supernumerary parathyroid gland, which also contributed to the persistent SHPT.